Transfer printing technologies and applications - Cao, Changhong; Sun, Yu (Elsevier, 2024)
Transfer printing (TP) is a class of techniques for the deterministic assembly of disparate micro/nanomaterials into functional devices, and has become an emerging suite of technologies for micro/nanofabrication. Systems enabled by transfer printing range from complex molecular-scale materials, to high-performance hard materials, to fully integrated devices. A variety of sub-techniques for different purposes have grown significantly in the past decade, leading to non-conventional electronics, optoelectronics, photovoltaics, and photonics, and enabling the development of non-planar and flexible electronics.Highlights breakthrough results and systems enabled by novel TP techniques.Highlights breakthrough results and systems enabled by novel TP techniques.Transfer Printing Technologies and Applications is a complete guide to transfer printing techniques and their cutting-edge applications. The first section of the book provides a solid grounding in transfer printing methods and the fundamentals behind these technologies. The second part of the book focuses on state-of-the-art applications enabled by transfer printing techniques, including areas such as flexible sensors, flexible transistors, wearable devices, thin film-based energy systems, flexible displays, microLED-based displays, metal films, and more. A concluding chapter addresses current challenges and future opportunities in this innovative field.Highlights breakthrough results and systems enabled by novel TP techniques.Highlights breakthrough results and systems enabled by novel TP techniques.This book is of interest to researchers and advanced students across nanotechnology, materials science, electrical engineering, mechanical engineering, chemistry, and biomedicine, as well as scientists, engineers, and R&D professionals involved with nanomaterials, micro- or nano-fabrication, microelectromechanical systems (MEMS), display technology, biotechnology, and devices